A Study of Microaggression and its Psychological and Physiological Effects on Individuals from Marginalised Communities (Journal of Social Sciences Review, 2023)
The psychological and physiological well-being of people is affected by an extensive range of circumstances. Although a single microaggression might appear innocuous, a lifetime of them can have a serious negative impact on someone's mental health. The research on microaggression and its psychological and physical impacts on people from marginalized communities in healthcare is reported in this publication. Two villages on AI reservations are involved in this community-based participatory study initiative. 130 adults participated in written surveys and interviews to gather data. More than one-third of the sample said they have come across a microaggression while interacting with their medical professionals. The self-reported histories of heart attacks, worse depressed symptoms, drug abuse, suicide cases, and preceding year hospitalization were all associated with complaints of microaggressions. In multivariate models, the connection between microaggressions and hospitalization (but just not a previous heart attack) seemed to be partially explained by assessments of depressive and drug abuse symptoms. In this research, microaggressions were linked to worse emotional and physiological health evaluations for Pakistani people living with a disease, undermining the principles of patient-centered care. Clinicians need to be aware of these subtly discriminatory behaviors, which are frequently unintentional.
Keywords: Discrimination; Marginalized; Drug Abuse; Healthcare; Depression; Mental; Microaggression